Phenotypic recapitulation and correction of desmoglein-2-deficient cardiomyopathy using human-induced pluripotent stem cell-derived cardiomyocytes. Issue 15 (5th May 2021) - Shiba, Mikio; Higo, Shuichiro; Kondo, Takumi; Li, Junjun; Liu, Li; Ikeda, Yoshihiko; Kohama, Yasuaki; Kameda, Satoshi; Tabata, Tomoka; Inoue, Hiroyuki; Nakamura, Satoki; Takeda, Maki; et al.
Abstract: Desmoglein-2, encoded by DSG2, is one of the desmosome proteins that maintain the structural integrity of tissues, including heart. Genetic mutations in DSG2 cause arrhythmogenic cardiomyopathy, mainly in an autosomal dominant manner. Here, we identified a homozygous stop-gain mutations in DSG2 (c.C355T, p.R119X) that led to complete desmoglein-2 deficiency in a patient with severe biventricular heart failure. Histological analysis revealed abnormal deposition of desmosome proteins, disrupted intercalated disk structures in the myocardium. Induced pluripotent stem cells (iPSCs) were generated from the patient (R119X-iPSC), and the mutated DSG2 gene locus was heterozygously corrected to a normal allele via homology-directed repair (HDR-iPSC). Both isogenic iPSCs were differentiated into cardiomyocytes [induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs)]. Multielectrode array analysis detected abnormal excitation in R119X-iPSC-CMs but not in HDR-iPSC-CMs. Micro-force testing of three-dimensional self-organized tissue rings (SOTRs) revealed tissue fragility and a weak maximum force in SOTRs from R119X-iPSC-CMs. Notably, these phenotypes were significantly recovered in HDR-iPSC-CMs. Myocardial fiber structures in R119X-iPSC-CMs were severely aberrant, and electron microscopic analysis confirmed that desmosomes were disrupted in these cells. Unexpectedly, the absence of desmoglein-2 in R119X-iPSC-CMs led to decreased expression of desmocollin-2 but no other desmosome proteins. Adeno-associated virus-mediated replacement of DSG2 significantly recovered the contraction force in SOTRs generated from R119X-iPSC-CMs. Our findings confirm the presence of a desmoglein-2-deficient cardiomyopathy among clinically diagnosed dilated cardiomyopathies. Recapitulation and correction of the disease phenotype using iPSC-CMs provide evidence to support the development of precision medicine and the proof of concept for gene replacement therapy for this cardiomyopathy. Graphical Abstract: